2006
DOI: 10.1002/marc.200600335
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Uniquely Branched Polyethylene by Anilinonaphthoquinone Ligated Nickel Complex Activated with Tris(pentafluorophenyl)borane

Abstract: Summary: A novel nickel complex ligated with 2‐(2,6‐diisopropylanilino)‐1,4‐naphthoquinone (1) was synthesized. The molecular structure of 1 determined by X‐ray analysis was a square‐planar geometry. Complex 1 conducted ethylene polymerization at 40 °C in a low activity to give linear polyethylene. On the other hand, 1 activated with 4 eq. of B(C6F5)3 was highly active for ethylene polymerization and gave a polymer possessing short chain branches of methyl, ethyl and propyl groups formed by a chain walking mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…Recently, cationic diimino-nickel complexes have been found to be active as procatalysts in ethylene polymerization and oligomerization [7]. Extensive investigations for new procatalysts of various late-transition metal complexes have been conducted [8], and nickel complexes bearing bidentate [9][10][11][12][13][14][15][16][17][18][19] or tridentate ligands [20][21][22][23][24] have been the focus of much research. Beyond our efforts for iron procatalysts in ethylene reactivity [25,26], some nickel procatalysts were also investigated and possessed good activities [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cationic diimino-nickel complexes have been found to be active as procatalysts in ethylene polymerization and oligomerization [7]. Extensive investigations for new procatalysts of various late-transition metal complexes have been conducted [8], and nickel complexes bearing bidentate [9][10][11][12][13][14][15][16][17][18][19] or tridentate ligands [20][21][22][23][24] have been the focus of much research. Beyond our efforts for iron procatalysts in ethylene reactivity [25,26], some nickel procatalysts were also investigated and possessed good activities [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…77 %). Effect of B(C 6 F 5 ) 3 for anilinotropone complex (7c) is also attributed to the zwitterionic catalyst [118,119].…”
Section: Catalyst Having Tropone-imide Type Ligandsmentioning
confidence: 96%
“…Shiono reported that Ni complex with an aminonaphthoquinone ligand (7c) catalyzes ethylene polymerization, producing methyl branched polyethylene [118,119]. Addition of B(C 6 F 5 ) 3 leads to increase of the catalytic activity and Benzyl Ni complex with a-iminocarboxamide ligand (7d) is formed by the reaction of potassium salt of the carboxyamide with the Ni complex having a p-benzyl ligand [120].…”
Section: Catalyst Having Tropone-imide Type Ligandsmentioning
confidence: 98%
See 1 more Smart Citation
“…23,31 Methyl branch was a dominant branch, while ethyl, propyl, butyl, amyl, and long branch were minor branches. The order of branch was methyl ) long > ethyl > propyl $ butyl > amyl, which was similar to the previous result.…”
mentioning
confidence: 99%